OCKHAM AND THE FUNCTION OF ABSTRACTION OCKHAM E A FUNÇÃO DA ABSTRAÇÃO - Rodrigo Guerizoli (Philósophos : Revista de Filosofia, 2011)
Abstraction was traditionally considered an essential element of any theory of cognition that denied that we are able to have an immediate intellectual apprehension of material things. From an historical point of view, however, this scenario of alternative – either abstraction or immediate intellectual apprehension of material things – was not assumed by several authors of the 14th century. The aim of the present study is to elucidate how and why one of these authors, William of Ockham (ca. 1285-1347), employed in his theory on the mechanisms of human cognition both intuition and abstraction. In order to carry out this project, several texts of Ockham and his interpreters will be analyzed. A abstração foi tradicionalmente considerada um elemento essencial de qualquer teoria do conhecimento que negasse que somos capazes de possuir uma apreensão intelectual imediata das coisas materiais. Desde um ponto de vista histórico, porém, esse cenário de alternativa – ou abstração ou apreensão intelectual imediata das coisas materiais – não foi assumido por diversos autores do século XIV. O objetivo do presente estudo é elucidar o como e o porquê de um desses autores, Guilherme de Ockham (ca. 1285-1347), ter empregado ambos, intuição e abstração, em sua teoria dos mecanismos da cognição humana. Para que se cumpra tal meta serão analisados diversos textos de Ockham e de seus intérpretes.